Elaboración de una crema cicatrizante a partir de mático, llantén, sábila y verbena. - Blacio Agurto, Carolina E. (2009)
In the antiquity it was used with more frequency the medicinal plants and due to the technological development we no longer give him the due importance of these plants. Because more people use chemical medications that natural products. In the homes medicinal, due plants are no longer cultivated that has gotten lost the habit of using the natural thing maybe the lack of the time or the ignorance of the use of healing plants.